Information asymmetry and investment efficiency : the role of blockholders - Mubashir Ali, Khan; Josephine Tan Hwang, Yau; Aitzaz Ahsan, Alias Sarang; Ammar, Ali Gull; Muzhar, Javed (Emerald Publishing Limited, 2025)
Purpose – This study aims to examine the extent to which information asymmetry affects investment efficiency and whether the presence of blockholders moderate this relationship. Design/methodology/approach –We employ the data of firms listed on the Malaysian stock exchange for the period 2010–2018, to compose our sample. Our final sample includes the 100 largest non-financial firms based on market capitalization. Collectively, these 100 companies contribute 84.2% to the total market capitalization (MYR 1,730bn) which is representative of the whole market. The ordinary least squares regressions were used as the main estimation technique. The system generalized method of moments, twostage least squares and propensity score matching were also used, to address potential endogeneity concerns. Findings – We document a positively significant association of information asymmetry with investment inefficiency. These results imply that information asymmetry reduces investment efficiency and enhances suboptimal investments. We also document that blockholders negatively moderate the relationship of information asymmetry with investment inefficiency. Further analyses show that investment inefficiency is higher in low growth firms than in high-growth firms because of higher information asymmetry. Research limitations/implications – We focus on Malaysia, which is a predominantly common-law Anglo-Saxon country. Graff (2008) documented that the investors are treated differently across legal systems and there are differences between the continental European and Anglo-Saxon countries. La Porta et al. (1999) documented that investors tend to have more legal protection in Anglo-Saxon countries. Therefore, our results may not be generalized to countries with different legal systems. Practical implications – An important implication of our findings is that stakeholders may encourage the presence of blockholders and give them a voice to weaken the positive relationship between information asymmetry and investment inefficiency.